Increased plasma cyclic nucleotide concentrations in congestive heart failure. Issue 5 (November 1984) - Ogawa, K; Shiozu, H; Mizuno, K; Ban, M; Ito, T; Satake, T
Abstract : Plasma concentrations of cyclic nucleotides (adenosine monophosphate (AMP) and guanosine monophosphate (GMP) were measured by an ultrasensitive radioimmunoassay in 138 patients with heart failure due to various causes. Measurements were related to the New York Heart Association classification of symptoms, plasma noradrenaline concentrations, and mean pulmonary artery pressures. Serial concentrations of cyclic AMP and GMP were also measured daily in four patients treated for acute left ventricular failure. Plasma concentrations of cycle AMP were related to the severity of the heart failure, plasma noradrenaline concentrations, and pulmonary artery pressures. Cyclic AMP concentrations fell rapidly after treatment of acute left ventricular failure. Plasma concentrations of cyclic GMP also depended on the severity of heart failure and the pulmonary artery pressure, and decreased sharply with treatment although remaining at a high value. The cyclic GMP concentrations were significantly higher in patients with mitral stenosis than in those with other types of heart failure.